2018
DOI: 10.1080/02770903.2018.1514630
|View full text |Cite
|
Sign up to set email alerts
|

Asthma dissemination around patient-centered treatments in North Carolina (ADAPT-NC): a cluster randomized control trial evaluating dissemination of an evidence-based shared decision-making intervention for asthma management

Abstract: Tapp (2019) Asthma dissemination around patient-centered treatments in North Carolina (ADAPT-NC): a cluster randomized control trial evaluating dissemination of an evidence-based shared decision-making intervention for asthma management,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
(48 reference statements)
0
15
0
Order By: Relevance
“…Since the recording and consenting of calls began after the third monthly group call, not all information about the different types of dissemination of information could be captured from all calls. While the design of our trial compared different dissemination methods,29 31 dissemination of information could not be correlated by practice to the outcomes data since Medicaid data was only collected for patients at each practice in the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the recording and consenting of calls began after the third monthly group call, not all information about the different types of dissemination of information could be captured from all calls. While the design of our trial compared different dissemination methods,29 31 dissemination of information could not be correlated by practice to the outcomes data since Medicaid data was only collected for patients at each practice in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection for this study revolved around recording monthly group calls to discuss a 12-week roll-out to implement the asthma SDM intervention into 10 primary care practices across North Carolina as part of the Asthma Dissemination Around Patient-centered Treatments in North Carolina Study using PFs 1 29 31 32. The research team invited providers and clinical staff from 10 primary care practices across the state (figure 1) to participate in a monthly group call with their PFs beginning in August 2014.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From earlier work, we demonstrated that a facilitated approach to implementation of SDM was associated with improved perceptions of SDM and improved ED utilization for pediatric patients [17,18,[27][28][29]. Identified implementation barriers included time constraints of the clinical team in a volume-based reimbursement structure, staff turnover, and lack of availability of staff to train as health coaches.…”
Section: Introductionmentioning
confidence: 94%
“…The patient and provider then discuss several evidence-based options and work towards an agreement on a treatment regimen [25,26]. This SDM process has been shown to improve medication adherence and clinically relevant disease outcomes for patients with asthma [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%